Legal impacts of the concept of entrepreneurship on the level of normative regulatory concentration in the telecommunication sector: the Actium case - Gomes, André Moura (Law, State and Telecommunications Review, 2010)
This work addresses the interaction between legal regulation and the concept of entrepreneurship by analyzing its institutional meaning and verifying the impact of its use as a reason in a case from the telecommunication sector, the so-called “Actium” case. The case refers to a request for authorization to provide a telecommunication service, rejected by the National Telecommunications Agency as it ruled there was no regulatory support for that purpose. This article is divided in four topics: in the first part, we demonstrate that the legal regulation for a certain activity varies according to the applicable level of normative and operational regulatory concentration. This concept presented by Herren Aguillar refers to the interpretation of the State regulatory activity as a spectrum of possible ways of acting, varying between opening normative spheres to private actors and State intervention. In the second part, the functional elements of the entrepreneurial phenomenon as organized by Michael Peneder are presented, and connected to risk bearing, market coordination, technology diffusion, innovation and so forth. We demonstrate they are legally relevant as related to freedom of trade and commerce and competition law principles. Then, we describe the relevant facts of the “Actium” case, and analyze the legal consequences of using the concept of entrepreneurship to the case, especially to the meaning of the equal protection of law in this context. Finally, we conclude that the concept of entrepreneurship is legally relevant, and its use may impact the level of normative regulatory concentration applicable to a given telecommunication service.